Peningkatan Kemampuan Roll Ke Depan Melalui Metode Pembelajaran Berbasis Permainan - Suherman, Suherman; Bismar, Ahmad Rum; Ridwan, Andi; Hudain, Muh. Adnan; Juhanis, Juhanis (Prodi Pendidikan Jasmani dan Olahraga, 2025)
This classroom action research (CAR) consisted of two cycles, aiming to improve forward roll ability through game- based learning in grade 5 students of SDN 78 Birea, Bantaeng Regency. The study involved 20 students using a total sampling technique. Data were collected through treatment with game-based learning and observation of forward roll performance in floor gymnastics. Data analysis used descriptive statistics with percentages.Results showed an improvement in forward roll ability from cycle I to cycle II. In cycle I, the completeness rate was 75%, increasing to 95% in cycle II. The average score also rose from 74 in cycle I to 82 in cycle II. These findings indicate that game-based learning effectively enhances forward roll ability in grade 5 students of SDN 78 Birea, Bantaeng Regency.